The Impact of Smoking, Alcohol Use, Recurrent Disease, and Age on the Development of Neck Fibrosis in Head and Neck Cancer Patients Following Radiation Therapy - Pratson, Connor L.; Larkins, Michael C.; Karimian, Brandon H.; Curtis, Caitrin M.; Lepera, Pamela A.; Brodish, Brian N.; Ju, Andrew W. (Frontiers in Oncology, 2021)
There is a paucity of information regarding the demographic factors associated with the development of neck fibrosis in head and neck cancer (HNC) patients following radiotherapy. A retrospective review of all patients being treated for HNC at a tertiary care center between 2013 and 2017 was performed. Chi-squared and Mann-Whitney U tests were used to identify differences in incidence and grade of fibrosis, respectively, between populations. A total of 90 patients aged 19 to 99 years were included. Factors associated with an increased incidence of fibrosis included smoking during radiotherapy (p < 0.001), alcohol use (p = 0.026), recurrent disease (p = 0.042), and age less than 60 (p < 0.001) on univariate analysis. Factors associated with increased grade of fibrosis in HNC patients included recurrent HNC (p = 0.033), alcohol use (p = 0.013), patient age younger than 60 years (p = 0.018), smoking during radiotherapy (p < 0.001), and non-Caucasian race (p = 0.012). Identification and intervention directed at patients that possess risk factors associated with fibrosis prior to treatment has the potential to improve the long-term quality of life for HNC patients.